Regioselective electrophilic aromatic borylation as a method for synthesising sterically hindered benzothiadiazole fluorophores. Issue 9 (16th February 2023) - Taylor, Dominic; Malcomson, Thomas; Zhakeyev, Adilet; Rosair, Georgina M.; Paterson, Martin J.; Marques-Hueso, Jose; Dalgarno, Scott J.; Vilela, Filipe
Abstract : A regioselective one-pot, three-step phenylation strategy has been applied to 4, 7-diarylbenzo[ c ][1, 2, 5]thiadiazoles to restrict internal bond rotation and alter the molecules' fluorescence properties. Abstract : Regioselective stepwise phenylation of 4, 7-diarylbenzo[ c ][1, 2, 5]thiadiazole fluorophores has been achieved through a facile one-pot, three-step synthetic strategy involving sequential borylation, hydroxydechlorination and Suzuki–Miyaura cross-coupling reactions. Crucial to the selectivity was the use of BCl3 to regioselectively install a boronic acid group in the ortho -position of only one of the diaryl groups. The subsequent introduction of ortho -phenyl groups through Suzuki–Miyaura cross-coupling gave rise to twisted structures with hindered intramolecular rotation, providing a structural lever with which the fluorophore absorption and emission properties could be adjusted.